The strongest link in a weak team? Performance of players with and without outside options in relegated football clubs - Michael Müller (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2016)
In this study the performance of players in relegated German football clubs is analysed, in particular the change in their contribution to team production. The players in the data sample differ regarding their outside options. Different career opportunities of players may have two effects when their current team struggles against relegation. First, players with outside options should be less motivated compared to the reference group. Second, risk attitudes of players who lack career opportunities may change. The empirical results show that players with outside options contribute less to the teams overall running distance before they are transferred to league opponents. Players who stayed after relegation with their teams played more incomplete passes, which indicates that they are more willing to take risks. Effort levels of staying players get higher, but leaving players might have superior playing talent. – – In diesem Beitrag wird die Leistung von Fußballern in absteigenden Bundesligavereinen untersucht, insbesondere die Veränderung in ihrem Beitrag zur Teamproduktion. Die Spieler im Datensatz unterscheiden sich hinsichtlich ihrer externen Optionen. Unterschiedliche Karrieremöglichkeiten von Fußballern könnten zwei Effekte haben, wenn ihr gegenwärtiger Verein gegen den Abstieg kämpft. Erstens sollten Spieler mit Angeboten von anderen Vereinen weniger motiviert sein. Zweitens könnte sich die Risikoeinstellung von Spielern ohne Transferanfragen ändern. Die empirischen Ergebnisse zeigen, dass der Anteil an der insgesamt vom jeweiligen Team zurückgelegten Laufdistanz für Fußballer niedriger ist, die ihre Vereine nach einem Ligaabstieg verlassen. Die Fehlpassquote der Spieler, die bei ihren Vereinen verbleiben, ist höher, was darauf hindeutet, dass ihre Risikobereitschaft steigt. Die Anstrengung verbleibender Spieler nimmt zu, doch abgehende Fußballer könnten ein größeres Spieltalent haben.
Keywords: Z20; Z22; J24; J63; M51; L83; 650; Sportler; Arbeitsgruppe; Arbeitsleistung; Karriereplanung; Risikopräferenz; Fußball; Sportorganisation; Deutschland